2012
DOI: 10.1016/j.cattod.2011.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the catalyst loading on the activity and the CO selectivity of supported Ru catalysts in the selective methanation of CO in CO2 containing feed gases

Abstract: We have investigated the methanation of CO and CO 2 over Ru/zeolite catalysts with different Ru loading in semi-realistic reformate gases by in situ X-ray absorption spectroscopy (XAS), in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) and kinetic measurements. Increasing the Ru loading causes an increase of the mean particle size from 0.9 nm (2.2 wt.% Ru) to 1.9 nm (5.6 wt.% Ru). At the same time, also the activity for CO methanation increases, while the selectivity for CO methanati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
79
1
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 58 publications
15
79
1
5
Order By: Relevance
“…On the other hand, it is well known that CO adsorption is weaker on smaller Ru particles than that on larger ones. [18] In total,t his results in al ower CO ad coverage for Ru/Al 2 O 3 with smaller Ru particles under otherwise identical, dry reaction conditions.…”
Section: Time Evolution Of the Adlayermentioning
confidence: 92%
“…On the other hand, it is well known that CO adsorption is weaker on smaller Ru particles than that on larger ones. [18] In total,t his results in al ower CO ad coverage for Ru/Al 2 O 3 with smaller Ru particles under otherwise identical, dry reaction conditions.…”
Section: Time Evolution Of the Adlayermentioning
confidence: 92%
“…Ni is the most studied and considered the most suitable catalyst for methanation of carbon oxides because of its high selectivity for CH 4 and its relatively low price [91][92][93][94]. Different support materials have been used for the dispersion of Ni and other active metals, including SiO 2 , Al 2 O 3 , TiO 2 , ZrO 2 , CeO 2 , and zeolite [95][96][97][98][99]. The activity and selectivity of the supported metal catalysts are strongly affected by the amount of metal loading, the size of the dispersed metal particles, the interactions between the support and the active species, and the composition of the support material [100].…”
Section: Cog Methanationmentioning
confidence: 99%
“…Okuhara et al [27] reported an increase of TOF of CO methanation as the dispersion of Ru decreased in Ru/Al 2 O 3 systems. Eckle et al [29] discovered that increasing the Ru mean particle size from 0.9 to 1.9 nm causes an increase of activity for CO methanation over Ru/zeolite catalysts. Extended studies performed by Panagiotopoulou et al [13] demonstrated that TOF of CO/CO 2 hydrogenation over Ru catalysts depends on the metal crystallite size.…”
Section: Co Hydrogenationmentioning
confidence: 99%